PENGARUH FINANCIAL LITERACY, LIFESTYLE, SELF CONTROL, CONFORMITY, DAN SELF ESTEEM TERHADAP CONSUMPTIVE BEHAVIOUR PADA GENERASI Z PENGGEMAR KOREAN WAVE DI KABUPATEN SIDOARJO - Choirunnisa, Rahma; Kusumaningrum, Trias Madanika (Universitas Negeri Surabaya, 2024)
This study examines the influence of financial literacy, lifestyle, self-control, conformity, and self-esteem on consumptive behaviour in Generation Z Korean wave fans in the Sidoarjo district. The data collection technique used purposive sampling and quota sampling with 231 respondents of Generation Z Korean wave fans in the Sidoarjo district. Data collection was carried out by distributing questionnaires online. This study uses Structural Equation Modeling (SEM) analysis techniques on AMOS version 24 software to produce conclusive causal relationships. The results of this study indicate that lifestyle and self-control significantly affect consumptive behaviour. While financial literacy, conformity, and self-esteem are insignificant to consumptive behaviour. This research is expected to provide an attitude that is not excessive to the development of Korean culture so that changes in habits and behaviour do not impact excessive lifestyle. This can lead to financial problems, such as increased debt levels or difficulty saving, stress, and anxiety related to economic conditions. Generation Z Korean Wave fans in Sidoarjo Regency are expected to increase self-control, be wiser in financial management decisions, and regulate consumption behaviour by needs, not just satisfy desires.